1991
DOI: 10.1128/jb.173.12.3803-3806.1991
|View full text |Cite
|
Sign up to set email alerts
|

The cis-acting regulatory element of the mvaAB operon of Pseudomonas mevalonii

Abstract: DNA upstream of the transcription start site of the mvaAB operon of Pseudomonas mevalonii, which encodes 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase (EC 1.1.1.88) and HMG-CoA lyase (EC 4.1.3.4), contains a cis-acting regulatory element which functions in the response to mevalonate. The regulatory element resides within a 36-bp region located from 48 to 84 bp upstream of the transcription start site of mvaA.This location was inferred from the P-galactosidase activities of P. mevalonii harboring p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…MvaT was shown to bind to a region located at positions Ϫ48 to Ϫ84 upstream from the mvaA translational start codon (39). Analysis of the cupA1 promoter regions, as well as those of cupB1, cupC1, and lecA, analyzed since they also appeared to be down-regulated by MvaT, failed to identify any significant regions of homology with the mvaA cis-acting element.…”
Section: Discussionmentioning
confidence: 99%
“…MvaT was shown to bind to a region located at positions Ϫ48 to Ϫ84 upstream from the mvaA translational start codon (39). Analysis of the cupA1 promoter regions, as well as those of cupB1, cupC1, and lecA, analyzed since they also appeared to be down-regulated by MvaT, failed to identify any significant regions of homology with the mvaA cis-acting element.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of transcription requires a 36-bp cis-regulatory DNA element located at -48 to -84 bp upstream of the AUG start codon of the mvaA gene . Mobility shift assays revealed that this cis-regulatory DNA element is bound in a specific fashion by a P. mevalonii protein (Wang & Rodwell, 1991) that we term MvaT. Sequence of the double-stranded oligonucleotide Probe A formed from the complementary single-stranded oligonucleotides 1493D and 1494D.…”
mentioning
confidence: 99%